The Integral, a Vision of its Evolution Through Time IV. Harmonic Analysis, Stochastic Processes. Stochastic Integration - Ortiz Fernández, Alejandro (2024)
The objective of this article is to give an overview of the relationship between harmonic analysis and stochastic processes, a relationship that has motivated many investigations and applications to specific problems. We will also emphasize stochastic integration.